EFL MALE AND FEMALE STUDENTS’ PERCEPTION ON SPEAKING ANXIETY IN CLASS-ORAL PRESENTATIONS - Debby Almira; Etika Rachmawati; Didih Faridah (Universitas Galuh, 2018)
The study attempted to investigate the perceptions of EFL male and female students about speaking anxiety in class-oral presentations and the strategies of EFL male and female students do to handle their speaking anxiety in class-oral presentations. Afterwarrds, the writer set forth two research questions: (1) What are the perceptions of EFL male and female students about speaking anxiety in class-oral presentations? (2) What are the strategies of EFL male and female students do to handle their speaking anxiety in class-oral presentations?. This study employed qualitative strategies by using case study. The participants were 30 second grade students which consists of 15 male and 15 female students from one of private university in Ciamis. The results for the first research question found that male and female students always felt anxiety if they should present a presentation at class and that anxiety was caused by some factors such as anxiety because of their selves, other students and their teachers. Moreover, the results for the second research question revealed that strategies used by students do to handle their speaking anxiety in class-oral presentations as follows. The first, trying to be confident. The second, making the atmosphere more cheerful. The third, well prepare. Finally, it is expected that class-oral presentations make the students feel anxious but still could handle their speaking anxiety with several strategies. Besides, it is suggested for further teachers to find out some technique to improve their ability in teaching English and must consider the aspect of students’ psychology such as anxiety and motivation when they teach. . Keywords: speaking anxiety, gender, perception, class-oral presentations